Building an Inclusive Digital Public Infrastructure: A Strategy for Strengthening Governance - Rahmatullah, Andi; Akbar, Rina Kurniati (Asian Digital Governance Problems, 2025)
Purpose: This study explores the state of digital governance in Southeast Sulawesi, focusing on the regions of Kendari, Kolaka, and Buton. It aims to assess the disparities in digital infrastructure readiness, institutional capacity, and inclusivity in these areas and their implications for effective governance Subjects and Methods: The research employs a qualitative methodology, including document analysis, interviews, and participant observation, to examine the local implementation of national digital policies. Results: The findings reveal significant disparities in institutional readiness, technological integration, and citizen participation across the three regions. Kendari demonstrates stronger governance capacity, integrated digital systems, and higher public participation, while Kolaka and Buton continue facing infrastructure limitations, fragmented coordination, and low digital literacy. Collaborative initiatives involving universities and civil society organizations contributed positively to community engagement and digital inclusion. Conclusions: Sustainable digital governance requires institutional reform, inclusive participation, technological integration, and equitable capacity development to strengthen governance effectiveness and social equity in peripheral regions.